A porous carbon material for capturing palladium ions in high-level acidic waste liquid and a preparation method thereof
Patent Information
- Application Number
- CN202411746233.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-12-02
AI Technical Summary
[0005]本发明的目的是解决用于捕获高放酸性废液中钯离子的各类吸附剂材料均存在某一方面的缺陷,或是在高酸度和高放射性环境中的稳定性和耐久性不足,或是对钯离子的吸附选择性不足,或是吸附剂材料制备工艺复杂、价格昂贵等不足,提供一种制备工艺简单,成本低廉,用于捕获高放酸性废液中钯离子的选择性高、耐久性和稳定性强的多孔碳材料,以及该多孔碳材料的制备方法
[0018]本发明的多孔碳材料具有氮/氧/硫原子占比高、介孔比高、比表面积大、孔径分布范围宽等特点,用于捕获高放酸性废液中钯离子具有效率高、容量高、选择性高和稳定性好的优点,克服了以往固相捕获剂效率低、容量小、选择性差和稳定性差的问题;此外,本发明多孔碳材料的制备方法具有原料低廉、工艺简单等优点,易实现工业化生产。
Smart Images

Figure CN119327423B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of porous materials technology, specifically relating to a porous carbon material for capturing palladium ions in highly acidic wastewater and its preparation method. Background Technology
[0002] Palladium, a precious metal, is widely used in catalysis, sensing, electronic devices, and decoration due to its superior physicochemical properties, including high temperature resistance, oxidation resistance, corrosion resistance, high catalytic activity, and strong coordination ability. However, the concentration of palladium in the Earth's crust is low, ranging from 0.1 to 3 ng / g, and its distribution is uneven globally. In recent years, driven by the unprecedented growth of the mobile phone and automotive industries, the demand for palladium has increased rapidly, and the palladium shortage is expected to worsen. Therefore, separating and recovering palladium from waste resources can not only alleviate the palladium shortage but also significantly reduce environmental pressure. Highly acidic wastewater generated from spent fuel recycling processes contains a considerable amount of palladium. Extracting palladium from highly acidic wastewater not only helps to enrich limited palladium resources but also solves the difficult problems of vitrified nuclear waste storage technology.
[0003] Currently, methods such as solvent extraction, precipitation, membrane separation, electrochemical methods, and adsorption are used to extract palladium from highly radioactive acidic wastewater. Among these, adsorption is widely used in metal separation and enrichment due to its advantages of low cost, ease of operation, and environmental friendliness. The key to adsorption is the adsorbent material. Adsorbents for capturing palladium from highly radioactive acidic wastewater mainly include anion exchange resins, ligand-modified mesoporous silica, metal-organic frameworks, and porous organic polymers. However, highly radioactive acidic wastewater typically contains numerous metal ions and is characterized by high radioactivity and high acidity. The aforementioned adsorbent materials lack stability and durability in high-acidity and high-radioactivity environments, and their adsorption selectivity for palladium ions is not strong. For example, anion exchange resins and ligand-modified silica are prone to leaching of surface-active species in highly acidic wastewater (J. Environ. Chem. Eng., 2024, 12, 112402.; RSC Adv., 2017, 7, 30815-30838.); metal-organic frameworks have poor stability in highly acidic wastewater environments (Green Chem. Eng., 2024, 5, 187-204.; Chemosphere, 2024, 349, 140729.); porous organic polymers require expensive organic monomers and large amounts of toxic and harmful organic solvents during preparation, and the synthesis steps are relatively complex (Angew. Chem. Int. Ed., 2023, 62, e202305225.).
[0004] Compared to the aforementioned adsorbent materials, porous carbon materials possess advantages such as wide availability, low cost, high specific surface area, high porosity, tunable pore size, and good chemical and thermal stability. Porous carbon materials are widely used as adsorbents. However, a major drawback of porous carbon materials is their poor selectivity. To improve the adsorption selectivity of porous carbon materials, the literature (ACS Appl. Mater. Interfaces, 2023, 15, 40088-40099.) prepared sulfur-doped porous carbon materials, which exhibited good adsorption selectivity for noble metal silver ions. Patent CN114177920A prepared sulfur-doped carbon materials using dipotassium anthraquinone-1,8-disulfonic acid as a raw material, which showed good adsorption capacity and selectivity for gold ions under high acid conditions; however, due to the protonation of sulfur atoms under high acid conditions, the coordination and complexation ability of the sulfur atoms doped on the surface of the porous carbon material with palladium ions was significantly weakened. In addition, patent CN113893821A uses 2-aminothiazole as a carbon source to obtain nitrogen-sulfur-doped porous carbon materials through pyrolysis activation. However, the process of using 2-aminothiazole as a carbon source still has the problem of high raw material prices. Furthermore, the nitrogen-sulfur-doped porous carbon materials still cannot meet the requirements for capturing palladium ions in highly acidic waste liquid. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of various adsorbent materials used for capturing palladium ions in highly radioactive acidic wastewater, such as insufficient stability and durability in high acidity and high radioactivity environments, insufficient adsorption selectivity for palladium ions, or complex and expensive preparation processes. This invention provides a porous carbon material with a simple preparation process, low cost, high selectivity, durability, and strong stability for capturing palladium ions in highly radioactive acidic wastewater, as well as a method for preparing this porous carbon material.
[0006] The porous carbon material for capturing palladium ions in highly acidic wastewater provided by this invention is prepared by the following method:
[0007] Step 1: After uniformly dispersing glucose and melamine in pure water, transfer them to a high-pressure reactor and react at 120-200℃ for 12-24 hours. After the reaction is completed, cool to room temperature, collect the precipitate, and wash it with pure water and ethanol until the filtrate is colorless. Then dry it to obtain a black nitrogen / oxygen co-doped carbon precursor.
[0008] Step 2: The nitrogen / oxygen co-doped carbon precursor, activator, and co-activator are uniformly dispersed in pure water, dried, and ground until homogeneous. The homogeneous mixture is then placed in a high-temperature tube furnace and activated in an inert atmosphere using a gradient heating method. The gradient heating method is as follows: first, the temperature is raised from room temperature to 400-500℃ and held for 30-40 minutes, then the temperature is raised to 600-650℃ and held for 30-40 minutes, and finally the temperature is raised to 700-900℃ and held for 1-2 hours. After activation, the activated product is immersed in hydrochloric acid aqueous solution to remove impurities and then dried to obtain the porous carbon material.
[0009] In step 1 above, the preferred mass ratio of glucose to melamine is 1:0.5 to 5.
[0010] Furthermore, in step 1, it is preferable to react at 160–180°C in a high-pressure reactor for 12–24 hours.
[0011] In step 2 above, the preferred mass ratio of the nitrogen / oxygen co-doped carbon precursor, activator, and co-activator is 1:1 to 5:0.1 to 0.5. The activator is potassium hydroxide, and the co-activator is either ammonium bisulfate or ammonium sulfate.
[0012] Furthermore, in step 2, the preferred method of gradient heating is as follows: first, raise the temperature from room temperature to 450°C and hold for 30 minutes; then, continue heating to 650°C and hold for 30 minutes; finally, raise the temperature to 700–800°C and hold for 1 hour. Preferably, the gradient heating rate is 3–8°C / min.
[0013] In step 2 above, the inert atmosphere is either nitrogen or argon.
[0014] The porous carbon material provided by this invention has a nitrogen doping content of 5wt% to 15wt%, an oxygen doping content of 10wt% to 20wt%, and a sulfur doping content of 1wt% to 5wt%.
[0015] The porous carbon material provided by this invention can be used to selectively capture palladium ions in highly radioactive acidic wastewater. The concentration of HNO3 in the highly radioactive acidic wastewater is 1-6 mol / L, and the concentration of Pd(II) is 1 ng / L-100 mg / L.
[0016] Furthermore, the highly radioactive acidic waste liquid also contains any one or more metal ions selected from Li(I), Na(I), K(I), Mg(II), Co(II), Zn(II), Cu(II), Pb(II), Ba(II), Ni(II), Ca(II), Mn(II), Cd(II), Al(III), Cr(III), Nd(III), Fe(III), Ce(III), La(III), Ru(III), Ti(IV), Zr(IV), Nb(V), and Mo(VI).
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0018] The porous carbon material of this invention has the characteristics of high nitrogen / oxygen / sulfur atom ratio, high mesoporous ratio, large specific surface area, and wide pore size distribution range. It has the advantages of high efficiency, high capacity, high selectivity and good stability when used to capture palladium ions in highly radioactive acidic waste liquid, overcoming the problems of low efficiency, small capacity, poor selectivity and poor stability of previous solid phase capture agents. In addition, the preparation method of the porous carbon material of this invention has the advantages of low raw material cost and simple process, and can be easily realized for industrial production. Attached Figure Description
[0019] Figure 1 This is a scanning electron microscope image of the porous carbon material prepared in Example 1.
[0020] Figure 2 This is a bar chart showing the elemental composition of the porous carbon material prepared in Example 1.
[0021] Figure 3 This is the infrared spectrum of the porous carbon material prepared in Example 1.
[0022] Figure 4 is N2 adsorption-desorption isotherms and pore size distribution of the porous carbon material prepared in Example 1.
[0023] Figure 5 This is a graph showing the Pd(II) adsorption capacity of the porous carbon material prepared in Example 1 under different acidity conditions.
[0024] Figure 6 This is a diagram showing the Pd(II) adsorption capacity of the porous carbon material prepared in Example 1 after irradiation and after high-energy ray irradiation.
[0025] Figure 7 This is a Pd(II) adsorption selectivity diagram of the porous carbon material prepared in Example 1.
[0026] Figure 8 This is a graph showing the Pd(II) adsorption cycle stability and durability of the porous carbon material prepared in Example 1. Detailed Implementation
[0027] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and embodiments. The described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] Example 1
[0029] Step 1: Dissolve and disperse 6g of glucose and 3.25g of melamine in 40mL of pure water, then transfer it to a 100mL high-pressure reactor and stir at 180℃ for 12h under sealed conditions. After the reaction is completed and cooled to room temperature, collect the precipitate by suction filtration and wash it with pure water and ethanol until the filtrate is colorless. Then dry it in an oven at 80℃ for 12h to obtain a black nitrogen / oxygen co-doped carbon precursor.
[0030] Step 2: Dissolve 2g of nitrogen / oxygen co-doped carbon precursor, 6g of potassium hydroxide, and 0.2g of ammonium sulfate in 40mL of pure water. After stirring and dispersing evenly, dry the mixture at 80℃ and grind it evenly. Then, place the evenly ground mixture into a high-temperature tube furnace and activate it in a nitrogen atmosphere using a gradient heating method. The gradient heating method is as follows: heat from room temperature to 450℃ at a heating rate of 5℃ / min, hold for 30min, then continue heating to 650℃, hold for 30min, and finally heat to 700℃ and hold for 1h. After activation, immerse the activated product in a 1mol / L hydrochloric acid aqueous solution to remove impurities, wash it, and dry it at 80℃ for 12h to obtain nitrogen / oxygen / sulfur co-doped porous carbon material.
[0031] Depend on Figure 1 As can be seen, the porous carbon material obtained in this embodiment exhibits a distinct porous honeycomb structure. (From...) Figure 2 It can be seen that the nitrogen doping content of the obtained porous carbon material is 7.56 wt%, the oxygen doping content is 13.76 wt%, and the sulfur doping content is 1.70 wt%. Figure 3 3660cm -1 The broad absorption band at 1654 cm⁻¹ represents the vibrations of OH and NH groups in the obtained porous carbon material. -1 The absorption band that appears corresponds to the vibration of the C=C group, 1572 cm⁻¹. -1 The strong absorption bands are attributed to the vibrations of the C=O double bond, at 1548 and 1040 cm⁻¹. -1 The absorption band is attributed to the CN vibration, 1120 cm⁻¹ -1 The absorption bands at 1083 and 663 cm⁻¹ are attributed to CO vibrations. -1 The two absorption bands appearing at this point belong to the stretching vibrations of S=O and CS. Figure 4 is available. As can be seen, the isotherm curves of the obtained porous carbon material belong to a mixed type I and IV classification in IUPAC. Under low pressure (0.0–0.1 P / P0), the adsorption capacity of the porous carbon material increases sharply, indicating the presence of abundant micropores. Under moderate pressure (0.4–0.8 P / P0), a distinct H4-type hysteresis loop is observed, indicating the presence of abundant mesopores in the material. Furthermore, the rise in the adsorption curve near a relative pressure of 1.0 indicates the presence of macropores in the material; that is, the porous carbon material prepared in this embodiment has a hierarchical pore structure of micropores / mesopores / macropores. Its specific surface area was calculated to be 1932 μm using the BET method. 2 g -1 The pore volume was calculated to be 0.86 cm³ using the HK method. 3 g -1 .
[0032] Example 2
[0033] Step 1: Dissolve and disperse 6g glucose and 6g melamine in 40mL pure water, then transfer it to a 100mL high-pressure reactor and stir at 160℃ for 24h under sealed conditions. After the reaction is completed and cooled to room temperature, collect the precipitate by suction filtration, wash it with pure water and ethanol until the filtrate is colorless, and then dry it in an oven at 80℃ for 12h to obtain a black nitrogen / oxygen co-doped carbon precursor.
[0034] Step 2: Dissolve 2g of nitrogen / oxygen co-doped carbon precursor, 2g of potassium hydroxide, and 0.3g of ammonium sulfate in 40mL of pure water. After stirring and dispersing evenly, dry the mixture at 80℃ and grind it evenly. Then, place the evenly ground mixture into a high-temperature tube furnace and activate it in a nitrogen atmosphere using a gradient heating method. The gradient heating method is as follows: heat from room temperature to 450℃ at a heating rate of 5℃ / min, hold for 30min, then continue heating to 650℃, hold for 30min, and finally heat to 800℃ and hold for 1h. After activation, immerse the activated product in a 1mol / L hydrochloric acid aqueous solution to remove impurities, wash it, and dry it at 80℃ for 12h to obtain nitrogen / oxygen / sulfur co-doped porous carbon material. The porous carbon material has a nitrogen doping content of 8.48wt%, an oxygen doping content of 11.77wt%, and a sulfur doping content of 3.35wt%.
[0035] Example 3
[0036] Step 1: Dissolve and disperse 3g glucose and 6g melamine in 40mL pure water, then transfer it to a 100mL high-pressure reactor and stir at 180℃ for 24h under sealed conditions. After the reaction is completed and cooled to room temperature, collect the precipitate by suction filtration, wash it with pure water and ethanol until the filtrate is colorless, and then dry it in an oven at 80℃ for 12h to obtain a black nitrogen / oxygen co-doped carbon precursor.
[0037] Step 2: Dissolve 2g of nitrogen / oxygen co-doped carbon precursor, 6g of potassium hydroxide, and 0.2g of ammonium sulfate in 40mL of pure water. After stirring and dispersing evenly, dry the mixture at 80℃ and grind it evenly. Then, place the evenly ground mixture in a high-temperature tube furnace and activate it in a nitrogen atmosphere using a gradient heating method. The gradient heating method is as follows: heat from room temperature to 450℃ at a heating rate of 5℃ / min, hold for 30min, then continue heating to 650℃, hold for 30min, and finally heat to 750℃, hold for 1h. After activation, immerse the activated product in a 1mol / L hydrochloric acid aqueous solution to remove impurities, wash it, and dry it at 80℃ for 12h to obtain nitrogen / oxygen / sulfur co-doped porous carbon material. The porous carbon material has a nitrogen doping content of 13.35wt%, an oxygen doping content of 10.26wt%, and a sulfur doping content of 2.12wt%.
[0038] Example 4
[0039] The nitrogen / oxygen / sulfur co-doped porous carbon material obtained in Example 1 was used to capture palladium ions in highly acidic wastewater. The specific experiment is as follows:
[0040] 1. Effect of acidity on the palladium ion trapping performance of porous carbon materials
[0041] 10 mg of porous carbon material was immersed in 50 mL of a 40 mg / L solution. -1 Pd(II) solutions were added to HNO3 solutions (HNO3 concentrations of 0.5 M, 1 M, 2 M, 3 M, 4 M, 5 M, and 6 M, respectively). The solutions were continuously shaken at 180 rpm and 35 °C for 8 h to reach adsorption equilibrium. After filtration, the Pd(II) concentration in the solutions was determined by inductively coupled plasma mass spectrometry (ICP-MS), and the adsorption capacity was calculated. The results are shown in [Figure number missing]. Figure 5 .Depend on Figure 5 It is evident that the adsorption capacity of porous carbon materials for Pd(II) gradually decreases with increasing HNO3 concentration, reaching 112.8 mg g when the HNO3 concentration is 0.5 M. -1 When the HNO3 concentration reaches 6M, the adsorption capacity is 51.4 mg g. -1 .
[0042] 2. Effects of high-energy ray irradiation on the palladium ion trapping performance of porous carbon materials
[0043] One g of porous carbon material was exposed to high-energy gamma rays at a dose rate of 1800 Gy / h. -1 The total dose was 100 kGy. 10 mg of irradiated porous carbon material was immersed in 50 mL of a solution containing 40 mg L... -1 Pd(II) solutions were added to HNO3 solutions (HNO3 concentrations of 3M and 6M, respectively), and the solutions were continuously shaken at 180 rpm and 35 °C for 8 h to reach adsorption equilibrium. After filtration, the Pd(II) concentration in the solution was determined by inductively coupled plasma mass spectrometry (ICP-MS), and the adsorption capacity was calculated. The results were compared with those of unirradiated porous carbon materials. Figure 6 .from Figure 6 As can be seen, the adsorption capacity of porous carbon materials for Pd(II) remains almost unchanged before and after irradiation.
[0044] 3. Selective adsorption of different metal ions by porous carbon materials
[0045] 10 mg of porous carbon material was added to 50 mL of a 3 M HNO3 solution containing a mixture of ions (Pd(II), Li(I), Na(I), K(I), Mg(II), Co(II), Zn(II), Cu(II), Pb(II), Ba(II), Ni(II), Ca(II), Mn(II), Cd(II), Al(III), Cr(III), Nd(III), Fe(III), Ce(III), La(III), Ru(III), Ti(IV), Zr(IV), Nb(V), Mo(VI)), with each ion having a concentration of 10 mg / L. -1 The solution was continuously shaken at 180 rpm and 35℃ for 8 hours to reach adsorption equilibrium. After filtration, the concentration of each ion in the solution was determined by inductively coupled plasma mass spectrometry (ICP-MS), and the adsorption capacity of each ion was calculated. The results are shown in [Figure number missing]. Figure 7 .from Figure 7 As can be seen, porous carbon materials exhibit high adsorption selectivity for Pd(II) and can capture Pd(II) from highly acidic waste liquid containing 25 complex ions.
[0046] 4. Stability and durability of porous carbon materials in capturing palladium ions
[0047] 10 mg of porous carbon material was immersed in 50 mL of solution containing 1 mg of L -1 In a 6M HNO3 solution of Pd(II), the solution was continuously shaken at 180 rpm and 35°C for 8 hours to reach adsorption equilibrium. The solution was then filtered, and the concentration of Pd(II) in the solution was determined by inductively coupled plasma mass spectrometry (ICP-MS), and the removal rate was calculated. Simultaneously, porous carbon material was collected by centrifugation. (0.1 mol L⁻¹) -1HNO3 and 1 mol L -1 Thiourea mixed eluent was used to elute the collected porous carbon material to desorb adsorbed Pd(II). After continuous shaking at 180 rpm and 35 °C for 12 h to achieve complete desorption, the concentration of Pd(II) in the eluent was determined by inductively coupled plasma mass spectrometry (ICP-MS), and the desorption rate was calculated. The eluted porous carbon material was collected by centrifugation, washed with deionized water and anhydrous ethanol, and then dried in a 60 °C oven for 12 h. The regenerated porous carbon material was subjected to the above adsorption-desorption experiment for 9 cycles. The results are shown in [Figure number missing]. Figure 8 .from Figure 8 As can be seen, porous carbon materials exhibit excellent cycle stability and durability in capturing Pd(II).
Claims
1. The use of porous carbon materials for capturing palladium ions in highly acidic wastewater, characterized in that: The porous carbon material has a nitrogen doping amount of 5wt% to 15wt%, an oxygen doping amount of 10wt% to 20wt%, and a sulfur doping amount of 1wt% to 5wt%, and the porous carbon material has a hierarchical pore structure of micropores, mesopores, and macropores. The porous carbon material is prepared by the following method: Step 1: After uniformly dispersing glucose and melamine in pure water, transfer them to a high-pressure reactor and react at 120-200℃ for 12-24 h. After the reaction is completed, cool to room temperature, collect the precipitate, and wash it with pure water and ethanol until the filtrate is colorless. Then dry it to obtain a black nitrogen / oxygen co-doped carbon precursor. Step 2: The nitrogen / oxygen co-doped carbon precursor, activator, and co-activator are uniformly dispersed in pure water, dried, and ground until homogeneous. The homogeneous mixture is then placed in a high-temperature tube furnace and activated in an inert atmosphere using a gradient heating method. The gradient heating method is as follows: first, the temperature is raised from room temperature to 400-500℃ and held for 30-40 min, then the temperature is raised to 600-650℃ and held for 30-40 min, and finally the temperature is raised to 700-900℃ and held for 1-2 h. After activation, the activated product is immersed in hydrochloric acid aqueous solution to remove impurities and then dried to obtain the porous carbon material. The activator is potassium hydroxide, and the co-activator is ammonium bisulfate or ammonium sulfate.
2. The use of the porous carbon material according to claim 1 for capturing palladium ions in highly acidic wastewater, characterized in that: In step 1, the mass ratio of glucose to melamine is 1:0.5 to 5.
3. The use of the porous carbon material according to claim 1 for capturing palladium ions in highly acidic wastewater, characterized in that: In step 1, the reaction is carried out at 160–180 °C for 12–24 h.
4. The use of the porous carbon material according to claim 1 for capturing palladium ions in highly acidic wastewater, characterized in that: In step 2, the mass ratio of the nitrogen / oxygen co-doped carbon precursor, activator, and co-activator is 1:1 to 5:0.1 to 0.
5.
5. The use of the porous carbon material according to claim 1 for capturing palladium ions in highly acidic wastewater, characterized in that: In step 2, the gradient heating method is as follows: first, the temperature is raised from room temperature to 450°C and held for 30 minutes, then the temperature is raised to 650°C and held for 30 minutes, and finally the temperature is raised to 700-800°C and held for 1 hour.
6. The use of the porous carbon material according to claim 1 for capturing palladium ions in highly acidic wastewater, characterized in that: In step 2, the gradient heating rate is 3–8 °C / min.
7. The use of the porous carbon material according to claim 1 for capturing palladium ions in highly acidic wastewater, characterized in that: In step 2, the inert atmosphere is either nitrogen or argon.
8. The use of the porous carbon material according to claim 1 for capturing palladium ions in highly acidic wastewater, characterized in that: The concentration of HNO3 in the highly acidic waste liquid is 1-6 mol / L, and the concentration of Pd is... 2+ The concentration ranges from 1 ng / L to 100 mg / L.
9. The use of the porous carbon material according to claim 8 for capturing palladium ions in highly acidic wastewater, characterized in that: The highly acidic waste liquid also contains Li. + Na + K + Mg 2+ Co 2+ Zn 2+ Cu 2+ Pb 2+ Ba 2+ Ni 2+ Ca 2+ Mn 2 + Cd 2+ Al 3+ Cr 3+ 、Nd 3+ Fe 3+ Ce 3+ La 3+ Ru 3+ Ti 4+ Zr 4+ 、Nb 5+ Mo 6+ Any one or more metal ions.
Citation Information
Patent Citations
Nitrogen and sulfur doped porous carbon material precious metal adsorbent and preparation method thereof
CN113893821A